(Why) Do You Like Scary Movies? A Review of the Empirical Research on Psychological Responses to Horror Films - Martin, G. Neil (Frontiers in Psychology, 2019)
Why do we watch and like horror films? Despite a century of horror film-making and en-tertainment, little research has examined the human motivation to watch fictional horror and how horror film influences individuals’ behavioural, cognitive and emotional re-sponses. This review provides the first synthesis of the empirical literature on the psy-chology of horror film using multi-disciplinary research from psychology, psychotherapy, communication studies, development studies, clinical psychology, and media studies. The paper considers the motivations for people’s decision to watch horror, why people enjoy horror, how individual differences influence responses to, and preference for, hor-ror film, how exposure to horror film changes behaviour, how horror film is designed to achieve its effects, why we fear and why we fear specific classes of stimuli, and how lik-ing for horror develops during childhood and adolescence. The literature suggests that (1) low empathy and fearfulness are associated with more enjoyment and desire to watch horror film but that specific dimensions of empathy are better predictors of people’s re-sponses than are others; (2) there is a positive relationship between sensation-seeking and horror enjoyment/preference but this relationship is not consistent; (3) men and boys prefer to watch, enjoy and seek our horror more than do women and girls; (4) women are more prone to disgust sensitivity or anxiety than are men and this may mediate the sex difference in the enjoyment of horror; (5) younger children are afraid of symbolic stimuli whereas older children become afraid of concrete or realistic stimuli; (6) in terms of coping with horror, physical coping strategies are more successful in younger children; priming with information about the feared object reduces fear and increases children’s enjoyment of frightening television and film. A number of limitations in the literature are identified, including the multifarious range of horror stimuli used in studies, disparities in methods, small sample sizes, and a lack of research on cross-cultural differences and similarities. Ideas for future research are explored.